OUTER MEMBRANE BIOGENESIS - Konovalova, Anna (Annu Rev Microbiol, 2017)
The hallmark of Gram-negative bacteria and organelles such as mitochondria and chloroplasts is the presence of an outer membrane (OM). In bacteria such as Escherichia coli, the OM is a unique asymmetric lipid bilayer with lipopolysaccharide (LPS) in the outer leaflet. Integral, transmembrane proteins assume a β-barrel structure (OMPs) and their assembly is catalyzed by the heteropentomeric Bam complex containing the OMP BamA and four lipoproteins, BamB-E. How the Bam complex assembles a great diversity of OMPs into a membrane without an obvious energy source is a particularly challenging problem because folding intermediates are predicted to be unstable in either an aqueous or a hydrophobic environment. Two models have been put forward, the budding model based largely on structural data, and the BamA-assisted model based on genetic and biochemical studies. Here we offer a critical discussion of the pros and cons of each.